Pencarian Rute Optimal Dengan Metode Steepest Ascent Hill Climbing Untuk Tempat Wisata Di Bandung Menggunakan Android - Youllia Indrawaty Nurhasanah; Ninda Halimah Alghoniyyah; Sofia Umaroh (Fakultas Teknik Universitas Hamzanwadi, 2021)
The lack of information on the path to tourist attractions makes tourists confused in choosing the shortest path. To overcome this, this study proposes an optimal route search system with the steepest ascent hill climbing method to find the most optimal route to tourist attractions. The search process for this tourist spot begins by looking for the latitude and longitude distance of each tourist spot along with the distance between tourist attractions using google maps, then the distance is entered into the steepest ascent hill climbing method with the initial stage of determining the number of combinations, where the combination results in the number of derivative trails. Then swap the initial path with the derivative path using graph theory. This process is repeated so that if the initial trajectory is smaller than the descended path, the effective route and route will be displayed on google maps. So based on the system testing conducted, the steepest ascent hill climbing method used as the main method of this research can be implemented in the search for the most effective or fastest route using the undirected graph method for the exchange process between tourist attractions